Offsite modular construction adoption in developing countries: Partial least square approach for sustainable future - Syed Saad; Kumeel Rasheed; Syed Ammad; Muhammad Hasnain; Habib Ullah; Abdul Hannan Qureshi; Aawag Mohsen Alawag; Muhammad Altaf; Touseef Sadiq (Ain Shams Engineering Journal)
The construction industry is significant in the economic growth of developing countries and is recognized globally for its high potential in sustainable development. Offsite Modular Construction (OMC) has the potential to revolutionize this sector. However, the adoption of OMC in developing nations remains limited due to various barriers. This study fills a critical gap by developing a novel framework that integrates the analysis of Offsite Modular Adoption Barriers (OMABs), i.e. resource availability, process management, and issues/perceptions, with the pursuit of overall sustainable future needs (OSFN) in residential projects. For this study, 314 construction specialists in Malaysia, a developing country with high construction activity, were surveyed. The study further employs PLS-SEM for latent variable relationship identification between OMABs and OSFN, which has not been researched comprehensively in the literature. The study reveals that there is a moderate positive correlation between OMABs and 33.6 % of the sustainable outcomes in residential projects. The path coefficient (β = 0.316) also provides evidence of the importance of eliminating these barriers in improving sustainability goals. This research is innovative in its approach as it seeks to address both the issues of OMC and sustainability in the developing nations. It is highly beneficial for policymakers as it provides a clear guideline on how to improve the OMC usage and promote sustainable construction. The SEM model can be used as a reference for other developing economies that are interested in the modernization of the construction industry for sustainable development.